Learning Strategies for Developing Numeracy in Children Aged 5-6 Years Through Dakon Games - Komiyanti, K; Fitriyah, Qonitah Faizatul (Universitas Muhammadiyah Surakarta, 2025)
Purpose This study aims to describe in depth the learning strategies applied by teachers in developing the numeracy skills of children aged 5-6 years and to analyze the effectiveness of the traditional dakon game as a medium for numeracy learning.Methodology This type of research uses a descriptive qualitative approach with an in-depth and comprehensive case study design on a particular phenomenon. The research was conducted in the odd semester of the 2025/2026 academic year (July-August 2026) at ABA Bengkle Kindergarten, Bengkle Hamlet, Semarang Regency. The object of the research is the Traditional Game Dakon, with the research subjects being 5-6 year old children of ABA Bengkle Kindergarten. Data were collected through field data sources obtained through direct observation, involving children and teachers as informants.Results The results of the study showed that effective learning strategies involved apperception and demonstration, small group formation, scaffolding/mentoring, and simple question and answer sessions that were repeated (2-3 times the game). The dakon game was proven to be effective in developing various aspects of numeracy, including counting skills, the concept of more or less, logical thinking and problem solving, and recognizing patterns. Data analysis confirmed that dakon was very effective as a numeracy medium, marked by significant improvements in focus, motivation, and increased children's ability to recognize the concept of more or less, count fluently, and solve simple problems.Applications/Originality/Value This research to analyze in depth the instructional strategies employed by teachers in developing early numeracy skills of children age 5-6 years through the traditional game dakon, specifically, the research to identify the forms of pedagogical the aspect of numeracy developed through the game, and evaluate the effectiveness of dakon as a culturally grounded learning context for fostering early numeracy in early childhood education.